Worms, wonderful worms - Atkinson, Kathie (Nelson Australia South Melbourne, Vic., 1994)
Introduces some of the different kinds of worm which make their home in or near the sea, including the fire worm, giant beach worm and Christmas tree worm. Suggested level: junior, primary